An Examination of Paraoxonase 1 Gene Polymorphism in Cases of Chronic Otitis Media - Durmuş, Kasım; Küçük Kurtulgan, Hande; Bora, Adem; Ejder Yıldırım, Malik; Elif Altuntaş, Emine (ENT Updates, 2020)
Objective: Chronic otitis media (COM) is a multifactorial disorder, the pathogenesis of which has yet to be fully elucidated. Numerous aetiological factors, including genetics, eustachian tube dysfunction, autoimmunity, infection, osteoclastic activity, cytokines, endotoxins, and products of lipid peroxidation resulting from oxidative stress, have been proposed to explain the chronic inflammation which lies at the heart of the disorder. The aim of this study is to investigate a possible relationship between the pathogenesis of COM and polymorphism within the paraoxonase 1 (PON1) gene. Methods: We investigated 49 patients admitted to the Otorhinolaryngology Department of Cumhuriyet University and diagnosed with COM between September and November 2017. The control group consisted of 51 healthy individuals. Polymerase chain reaction (PCR) – restriction fragment length polymorphism (RFLP) methods were used to genotype the PON1 Q192R (rs662) polymorphism. Results: When the case and control groups were compared in terms of the existence of PON1 (Q192) polymorphism, there was no statistically significant difference between the groups (p=0.166, p>0.05). When intergroup comparison was performed on the type of PON1 (Q192) polymorphism, there was also no statistically significant difference (p=0.261, p>0.05). Conclusion: The present study is the first known study in which PON1 polymorphism has been examined in cases of COM. The results of our study failed to indicate a statistically significant relationship between PON1 polymorphism and COM. However, it is important to note that the higher rate of 192RR polymorphism within the control group may indicate a protective effect in COM.